Prospective lithium aluminosilicate glass-ceramic materials for pulse rangefinders - Savvova, O. V.; Tur, O. H.; Voronov, H. K.; Fesenko, O. I.; Babich, O. V.; Smyrnova, Yu. O. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The relevance of creating multi-functional nanosecond pulsed laser devices with a generation wavelength that lies in the conditionally eye-safe region of the spectrum of 1.5÷1.6 μm has been established. The prospects of using the mode of passive Q-switching when receiving powerful nanosecond laser pulses with a radiation divergence close to the diffraction one have been determined. Materials for shutters that function in the mode of passive Q-switching were analyzed: solid-state nonlinear optical materials based on single crystals of yttrium-aluminum garnet doped with cations of neodymium, chromium, vanadium and other Nd- or Yb-doped crystals in the wavelength range of 0.8–1.2 μm. The promising use of oxide single crystals activated by Co2+ ions in four-coordinated oxygen positions for MgAl2O4, LiGa5O8, LaMgAl11O19 has been confirmed. The feasibility of developing transparent glass-ceramics based on aluminomagnesium and lithium gallium spinel for pulsed ranging was determined, taking into account its commercial availability, the simplicity of the production technology, as well as the homogeneity of the distribution of the activator in the volume. The feasibility of creating a new type of nonlinear optical materials based on nanostructured heat-resistant lithium aluminosilicate glass ceramics with spinel nanocrystals activated by Co2+ ions under low-temperature heat treatment conditions, has been determined. The purpose and tasks of the work are formulated, which consist in justifying the choice of the system and compositions of glasses for obtaining glass-ceramic materials as a passive laser shutter for powerful lasers that operate at a wavelength of 1.54 μm and are characterized by high heat resistance. The choice of the lithium aluminosilicate system R2O – RO – RO2 – P2O5 – R2O3 – SiO2 based on phase-forming SiO2, Al2O3, Li2O, modifying K2O is substantiated; RO – MgO, ZnO, CaO, SrO, BaO components and a complex crystallization catalyst of P2O5, CeO2, TiO2, SnO2, ZrO2 and ZnO. The structural criteria for the glass matrix were formulated. Compositions of model glasses were designed taking into account the calculated parameters fSi > 0.22, Kсr ≥ 3.5, Ktr ≥ 2.1, and the probability of obtaining transparent glass-ceramic materials with a sitallized structure for pulse rangefinders was established on their basis.

Встановлена актуальність створення імпульсних наносекундних лазерних приладів поліфункціонального призначення з довжиною хвилі генерації, що лежить в умовно безпечній для зору області спектру 1,5÷1,6 мкм. Визначено перспективність використання режиму пасивної модуляції добротності при отриманні потужних наносекундних лазерних імпульсів з розбіжністю випромінювання, близькою до дифракційної. Проаналізовано матеріали для затворів, які функціонують у режимі пасивної модуляції добротності: твердотільні нелінійно оптичні матеріали на основі монокристалів ітрієво-алюмінієвого гранату легованого катіонами неодиму, хрому, ванадію та інших Nd- або Yb-легованих кристалів в діапазоні довжин хвилі 0,8 – 1,2 мкм. Підтверджена перспективність використання оксидних монокристалів, що активовані іонами Со2+ у чотирьох координованих киснем позиціях для MgAl2O4, LiGa5O8, LaMgAl11O19. Визначена доцільність розробки прозорої склокераміки на основі алюмомагнієвої та літієвогалієвої шпінелі для імпульсної дальнометрії, зважаючи на її комерційну доступність, простоту технології виробництва, а також однорідність розподілу активатора у об’ємі. Визначена доцільність створення нового типу нелінійно-оптичних матеріалів на основі наноструктурованої термостійкої літійалюмосилікатної склокераміки з нанокристалами шпінелі, які активовані іонами Со2+ в умовах низькотемпературної термічної обробки. Сформульовано мету та завдання роботи, які полягають у обґрунтуванні вибору системи та складів стекол для одержання склокристалічних матеріалів як пасивного лазерного затвору для потужних лазерів, які функціонують на довжині хвилі 1,54 мкм та відрізняються високою термостійкістю. Обґрунтовано вибір літійалюмосилікатної системи R2O – RO – RO2 – P2O5 – R2O3 – SiO2 на основі фазоутворюючих SiO2, Al2O3, Li2O, модифікуючих K2O; RO – MgO, ZnO, CaO, SrO, BaO компонентів та комплексного каталізатору кристалізації P2O5, CeO2, TiO2, SnO2, ZrO2 та ZnO, сформульовано структурні критерії до скломатриці. Спроектовано склади модельних стекол з урахуванням розрахованих показників fSi > 0,22, Ккр ≥ 3,5, Кпр ≥ 2,1 та встановлена вірогідність одержання на їх основі прозорих склокристалічних матеріалів із ситалізованою структурою для імпульсної дальнометрії.
Перспективні літійалюмосилікатні склокристалічні матеріали для імпульсної дальнометрії
Keywords: lithium aluminosilicate glasses; glass-ceramic materials; nanostructure; spinel; shutter; passive Q-switching; літійалюмосилікатні стекла; склокристалічні матеріали; наноструктура; шпінель; затвори; пасивна модуляція добротності